Madrid Conference: Promoting the Process of Lithuania Independence Case - Banionis, Juozas (Genocidas ir rezistencija, 2002)
Having lasted for about 96 weeks (8 November 1980–9 September 1983) in Madrid, the Conference on Security and Cooperation in Europe (SCE) further proceeded with the dialogue between East and West. The Lithuanians communities abroad considered this forum of significant importance to the process of Lithuania independence case., Seeking to raise the issue of occupation of the Baltic States, therefore, all the major political organizations (Supreme Committee for the Liberation of Lithuania VLIK, Council of American Lithuanians ALT, World Lithuanian Community WLC) were putting all efforts to influence the USA administration, the senate and the House of Representatives since the very end of the Belgrade Conference. In 1979 the USA Congress adopted a resolution where it was stated that the Helsinki agreements ensure the free self-determination right for the Baltic States. It was the third USA Congress document which discussed the Baltic independence case during the post-war period.
Keywords: Soviet occupation; emigree; emigree organizations; KGB; Madrid conference; Lithuanian liberation movement